Kinetics and DFT studies of photoredox carbon–carbon bond cleavage reactions by molecular vanadium catalysts under ambient conditions - Gazi, Sarifuddin (2018)
Visible light assisted photocatalytic organic reactions have recently received intense attention as a versatile approach to achieve selective chemical transformations, including C−C and several C−X (X = N, O, S) bond formations under mild reaction conditions. The light harvesters in previous reports predominantly comprise ruthenium or iridium photosensitizers. In contrast, selective, photocatalytic aliphatic C−C bond cleavage reactions are scarce. The present study focuses on rationally designing VV oxo complexes as molecular, photoredox catalysts toward the selective activation and cleavage of a C−C bond adjacent to the alcohol group in aliphatic alcoholic substrates. We have employed kinetics measurements and DFT calculations to develop a candidate for the catalytic C−C bond activation reaction that is up to 7 times faster than our original vanadium complex. We have also identified a substrate where the C−C bond cleaves at rates 2.5−17 times faster, depending on the catalyst used. In order to better understand the effects of ligand modification on the thermodynamics and catalysis, DFT calculations were employed to reveal the orbital energies, the electronic transitions during the C−C bond cleavage, and the activation barriers. Our combined kinetics and computational studies indicate that the incorporation of electron-withdrawing groups at select sites of the ligand is essential for the development of active and stable vanadium photocatalysts for our C−C bond cleavage reactions.